A Sociohistorical Reading on the Position of Disabled Individuals in the Grip of Modernization and the Market Economy - Fatih Kucur (Sosyal Siyaset Konferansları Dergisi)
The concept of being disabled has faced many definitions throughout history. In this regard, the concept of disability is based on the claim that being disabled is not a loss of ability but an issue of access. While this claim remains controversial, it has largely settled into the vernacular of the social sciences, however. How the use of this conceptual claim became widespread and its perspective in the social sciences was neither easy nor spontaneous. This study traces the conceptual transformation while discussing this process and reveals in a sociohistorical context how racial inequality based on the idea of Western superiority and the discourse on superior genes and people have caused repercussions regarding the issue of racial discrimination and the disabled. The study has adopted a descriptive approach in this regard and consulted the literature of this field, evaluating the process of looking at people and the body in general, as well as the disabled and society in a specific Western historical context from the sociohistorical perspective of being in the grip of modernization and the market economy. The study addresses the issue in this context by considering the transformation of the perspective toward humans and the disabled and the practical outcomes of this transformation. Thus, the study aims to contribute to understanding the adventure of the issue prior to the point currently reached and to make determinations about the founding mental background of the modern world.